Body Shaming in Online Space: Systematic Review - Kudlová, Karolína; Hollá, Katarína; Turzík, Justin; Hrkotáčová, Natália (Journal of Ecohumanism, 2024)
The main aim of this research paper is to synthesize previous studies and offer a thorough review of the selected body shaming research. Our study summarized the findings of 9 studies that addressed the issues of body shaming, body image, and appreance dissatisfaction in relation to the online space among adolescents and young adults. A systematic review and meta-analysis were conducted following the PRISMA guidelines. In the study, we primarily focused on the age and gender of the participants, protective and risk factors as well as the consequences in connection with the investigated issue. Consequences included low self-esteem, negative feelings related to one’s body image, anxiety, depression, shame, comparison, perfectionism about physical appearance, editing photos before sharing on social networks, etc. Interventions discuss positive results in self-compassion, which is directly related to body shaming and body-esteem from previous consequences. Aim The main aim of this research paper is to synthesize previous studies and offer a thorough review of the selected body shaming research. The frequent mentions of terms related to body image and self-esteem in the context of online media suggest a variety of negative consequences for individuals which speaks to the importance of mental health support for those affected by these issues . Methods This study summarized the findings of 9 studies that addressed the issues of body shaming, body image, and appreance dissatisfaction in relation to the online space among adolescents and young adults. The methodology describes the data collection procedure using the ASReview Lab system. A systematic review and meta-analysis were conducted following the PRISMA guidelines. The review we present includes a descriptive analysis of the data. The search strategy included searching abstracts of relevant studies. Automatic random selection was used to identify eligible studies. Abstracts were categorized as relevant or irrelevant according to the keywords entered. The selection process continued until a stopping criterion was reached. Results In the study, we primarily focused on the age and gender of the participants, protective and risk factors as well as the consequences in connection with the investigated issue. Consequences included low self-esteem, negative feelings related to one’s body image, anxiety, depression, shame, comparison, perfectionism about physical appearance, editing photos before sharing on social networks, etc. We perceive a correlation with individual consequences and interventions. Striving for positive changes and interventions can be considered as a direct response to the negative consequences mentioned above, such as body shame, low self-esteem, negative body perception, etc. Interventions discuss positive results in self-compassion, which is directly related to body shaming and body-esteem from previous consequences. Similarly, interventions with positive effects on body image are related to several already mentioned consequences, such as worse body image, dissatisfaction with appearance and negative perception of one’s own body. Conclusions: The findings suggest an equally high need for prevention strategies and educational interventions that promote media literacy and critical thinking skills for safer interactions in the online space among adolescents and young adults. We believe that our study will be an inspiration for further research, either by supplementing the systematic review with additional studies or empirical interventions in the form of prevention or interventions in connection with the examined issue of physical appearance and online space.